The fate of knowledge - Longino, Helen E. (New Jersey: Princeton University Press, 2002)
Seeking to break the deadlock in the ongoing wars between philosophers of science and sociologists of science, this text argues that social interaction actually assists us in securing firm, rationally-based knowledge, clarifying the philosophical points at issue.
Chapter One: Introduction: The Rational-Social Dichotomy 1 Chapter Two: Taking Social Studies of Science Seriously 11 Chapter Three: The Philosophers Respond 42 Chapter Four: Disassembling the Rational-Social Dichotomy 77 Chapter Five: Socializing Cognition 97 Chapter Six: Socializing Knowledge 124 Chapter Seven: Clarifications and Responses 145 Chapter Eight: Pluralism and Local Epistemolgies 175 Chapter Nine: Conclusion 203 References 215 Index 227
Includes bibliographical references and index.
Keywords: Knowledge, Sociology of